Calculation of three-body reaction kinematic and data processing by using Monte-Carlo method - O. M. Povoroznyk (Ядерна фізика та енергетика)
Method of calculation of the three-body reaction kinematic and treatment procedure of two-dimensional coincidence spectra for kinematically-complete investigation of the three-body reactions by using Monte-Cаrlo method is developed. Two-dimensional tt-coincidences spectra obtained from experimental research of three-body 3 Н(α, tt)p reactions for studies of the excited states of 4 Не with a t + p cluster structure are analyzed by these approaches. The excitation energies and widths for four lowest excited states of 4 Не are found.